Constraints on educational development : a Guyanese case study - Craig, Dennis R. (2006)
Addresses the problem of literature at the primary level through curriculum development, specifically the use of Skills Reinforcement Guides. Cites ineffective planning, personal jealousies, political interference and monopolisation of scarce resources as well as change of personnel amongst the fundamental constraints on educational improvement in a poor developing country.